Implementasi Sistem Penjaminan Mutu Internal Pada Perguruan Tinggi dalam Menghadapi Persaingan Global - Widiawati Widiawati; Asep Suryana; Hanif Alkadri (Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to describe and find objective evidence of the implementation of a quality assurance system in the Faculty of Education to serve as scientific findings and brainstorming for other faculties. This research is a quantitative descriptive study conducted, the research informants consisted of the dean, deputy dean, SKM, and GKM Team of UPI Bandung Faculty of Education. Research data were collected through interviews, observation, and documentation studies. The qualitative data analysis procedure was carried out through three stages, data reduction, data presentation, and drawing conclusions and data verification. The results of the study show that FIP UPI has a quality policy that is used as a reference/guideline in carrying out internal quality assurance activities with reference to university policies. The PPEPP model is used as a model in implementing quality assurance. Quality assurance is a must for every university that wants to exist in the era of global competition, seeks to ensure that every existing quality meets or even exceeds the standard and continuous improvement can be made. Awareness and commitment in carrying out quality assurance still needs to be built by the UPI FIP academic community.